Mughal Kingdom in India according to Hamka's sejarah umat Islam - Abul Hassan Ashari, Mohamad Zulfazdlee; Mohd Nor, Mohd Roslan; Ahmad Safian, Nursafira; Safiai, Mohd Hafiz; Zainal, Hakim; Jamsari, Ezad Azraai (Morse Florse, 2021)
India is important in the study of Islamic history and civilization research as it was one of the earliest territories that received Islamic preaching and was the site for various Islamic kingdoms until the year 1857. The achievements of Islamic civilization in India, particularly during the Mughal era, added sparkle to the glory of Islamic history. For this reason, the facts relating the Mughal Kingdom in India have been discussed in writings on Islamic history and civilization, including the book, Sejarah Umat Islam, by Hamka. The purpose of this article is to study Hamka’s work on the history of the Mughal Kingdom in India and analyse the narration and discussion he submitted. This research adopts a qualitative approach using historial study and content analysis to gather and analyse data. Research results find that Hamka had the interest and knowledge in writing Islamic history by describing Muslim societies and Islamic states from their inception to their end, including the Mughal Kingdom in India. In his narrative of Mughal history, Hamka inserted the element of teaching or ibrah (lesson), particularly when discussing the time of Mughal decline. The narrative approach is consistent with the philosophy of Islamic history that stresses on the ibrah concept, which was meaningful to Hamka’s own personality as a missionary. Hence, his work, Sejarah Umat Islam, proved Hamka’s ability to discuss Islamic history, and simultaneously resonated with readers interested in issues of Islamic history.